A review of control architectures for autonomous navigation of mobile robots - Nakhaeinia, Danial; Tang, Sai Hong; Mohd Noor, Samsul Bahari; Motlagh, Omid (Academic Journals, 2011)
A mobile robot as an intelligent system needs to sense the surroundings, perceive the working environment, plan a trajectory and execute proper reaction using the information. Robotic control architectures define how these abilities should be integrated to construct and develop an autonomous navigation. The control architectures could be classified into three categories: Deliberative (Centralized) navigation, Reactive (Behaviour-based) navigation and hybrid (Deliberative - Reactive) navigation. This paper reviews various control architectures for autonomous navigation of mobile robots. The significance, advantages and drawbacks of the architectures are discussed and compared with each other.